"You Have Chosen Us from among All Nations": The Chosenness Concept in Israeli Ultra-Orthodox School Anthologies. Issue 4 (2nd October 2022) - Zighelboim, Oshri
ABSTRACT: This article presents a cognitive semantic investigation into the concept of the "Chosen People" in Israeli ultra-Orthodox anthologies. The article opens with a historical-theological review of chosenness and its distinctly separatist stance. The study, based on the understanding that "nationality" is a multilayered concept, identifies four types of separatism: territorial, ethnic, linguistic, and religious. Three of these are identified in ultra-Orthodox school anthologies (territorial, ethnic, and religious) and are explored in detail with anthology text excerpts. The article also includes a comparison of various education streams in Israel (state, state-religious and ultra-Orthodox) to examine how each addresses and is invested in the concept of chosenness. Finally, the article reveals the commonalities in the perception of victimhood that see the Jewish people as a persecuted and tormented minority throughout history.